IITA Research highlights for 1981 - International Institute for Tropical Agirculture (Ibadan International Institute for Tropical Agirculture, 1982)
The publication comprise of highlights of researches conducted by IITA Ibadan in 1982. These researches were conducted in the humid forest, transitional, and savannah zones of Nigeria. Areas included root and tuber crops, farming systems, grain legumes, cereals and training.
lje 14/06/17
Loans
Keywords: Agriculture-Tropical; Agriculture; Nigeria